ASSA13-14-13 The Relationship Between Expression of Adiponectin Including Its Receptor1 and Ventricular Remodelling in Spontaneously Hypertensive Rats. (29th April 2013) - Sun, R; Liu, Y; Sun, H; Qin, Y; Yang, R
Abstract : Objective: To observe the expression of the serum adiponectin hormone (APN) with myocardial adiponectin receptor 1 (AdipoR1) and the degree of insulin resistance (IR) in spontaneously hypertensive rats (SHR) in order to explore the relationship between the three aspects and elevation of blood pressure and ventricular remodelling. Methods: To select eight 22 years old rats of SHR and WKY respectively as objects of study and to measure its APN, FINS. To adopt immunohistochemistry to measure its distribution and protein expression of AdioR1. To adopt the method of actual time PCR to measure the mRNA expression of AdipoR 1 in myocardium. Results: compared with the same years old rats of WKY group, the systolic pressure and the degree of IR and the weight of heart and the mass index of left ventrice of SHR group are increased, and then the APN level of blood serum and the expression of protein and mRNA of myocardial AdipoR1 are decreased (P < 0.05). Conclusions: The rats of SHR group exist obvious ventricular remodelling. The expression of APN of blood serum and the expression of myocardial AdipoR1 are decreased. The degree of IR is increased. There may be relationship the ventricular remodelling and the under-expression of the APN level of Blood serum and the expression of myocardial AdipoR1.